Hubungan Konsistensi Budaya Organisasi Dengan Kelengkapan Dokumentasi Keperawatan: Manajemen Nyeri Di Rumah Sakit - Titiek Muhaeriwati; Rr. Tutik Sri Hariyati; Dewi Gayatri (STIKes RSPAD RSPAD Gatot Soebroto, 2018)
Complete documentation of pain management is the proof of implementation of the professional nurse and competency in administering nursing care of pain management in accordance with the standard. The purpose of the research is to identify the correlation of consistency of organizational culture which is perceived by the acting nurse with complete nursing documentation of pain management. This research applies the method of cross sectional which is measured by questionnaire and observation of nursing documentation in retrospective manner. The result of research indicate that the acting nurse perceive the consistency of organizational culture of 64.8%. Total complete nursing documentation of pain management is 72.51% and, the sub variable of pain assessment indicate the average of 7.07 (47.13%). The characteristic of acting nurse in sex, marital status and level of education is significant with complete nursing documentation of pain management. The consistency of organizational culture in the coordination and integration is significant with complete nursing documentation of pain management in the aspect of assessment p=0.037 (p=0.05), but the consistency of organizational culture in the aspect of core value and consensus is not significant. The conclusion proves that there is no significant correlation between the consistency of organizational culture with the complete nursing documentation of pain management. However, the consistency of organizational culture is significant with the complete nursing documentation of pain management only in the aspect of assessment p=0.036. The expectation of hospital is to prioritize the improvement of human resources of formal education to become professional nurse and competency as responsibility, and have critical thought in the complete nursing documentation, specifically the nursing documentation of pain management. Keywords: Consistency Of Organizational Culture; Pain Management And Nursing Process